ESTIMATION OF LEAD SOURCES IN A JAPANESE CEDAR ECOSYSTEM USING STABLE ISOTOPE ANALYSIS - Itoh Y.; Noguchi K.; Takahashi M.; Okamoto T.; Yoshinaga S. (My University, 2007)
Anthropogenic Pb affects the environment worldwide. To understand its effect on forest ecosystem, Pb isotope ratios were determined in precipitation, various components of vegetation, the forest floor, soil and parent material in a Japanese cedar (Cryptomeria japonica D. Don) forest stand. The average 206Pb/207Pb ratio in bulk precipitation was 1.14 ± 0.01 (mean ± SD), whereas that in the subsoil (20-130 cm) was 1.18 ± 0.01. Intermediate ratios ranging from 1.15 to 1.16 were observed in the vegetation, the forest floor, and the surface soil (0-10 cm). Using the 206Pb/207Pb ratios, the contribution of anthropogenic sources to Pb accumulated in the forest were estimated by the simple binary mixing model. Sixty-two percent of the Pb in the forest floor, 71% in the vegetation, and 55% in the surface soil (0-10 cm) originated from anthropogenic sources, but only 16% in the sub-surface soil (10-20 cm) was anthropogenic. These results suggest that internal Pb cycling occurs mainly between surface soil and vegetation in a Japanese cedar ecosystem, and that anthropogenic Pb strongly influences Pb cycling. Although the Japanese cedar ecosystem has a shallow forest floor, very little atmospherically derived Pb migrated downward over 10 cm in depth. © 2007 Elsevier Ltd. All rights reserved.